META ANALYSIS: THE EFFECTIVENESS AND INFLUENCE OF PROBLEM BASED LEARNING ON MATHEMATICS LEARNING - Yasin, Muhamad; Pujiastuti, Heni; Hendrayana, Aan; Syamsuri, Syamsuri (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Problem based learning is a learning model that is currently widely used in all circles. such as teachers, lecturers and research students. For this reason, researchers chose problem-based learning as the topic of this meta research. There are several criteria for selecting articles, namely: Form of publication, location of research, time span of publication and available statistical information. Empirical data were obtained from published articles identified through computer literature searches using electronic databases such as ERIC https://eric.ed.gov/?journals), SAGE Publishing (https://us.sagepub.com/en-us/nam /journals), and Google Scholar (https://scholar.google.co.id/schhp?hl=id). In addition, manual searches were carried out through library sources. Of all the articles, there were 12 articles that met the predetermined criteria, then analysis was carried out using the website https://www.meta-mar.com/, to obtain a large combined effect size. The conclusion is that the use of the PBL model in mathematics learning is very strong and the use of the PBL model helps students in teaching to deepen PBL for learning purposes and PBL can also increase the effectiveness and influence of learning even better